The Implementation of Project-Based Learning in Productive Skill Programs for the Development of 21st Century Vocational School Students - Samsudi, Samsudi; Supraptono, Eko; Sunyoto, Sunyoto; Rohman, Shohihatur (KnE Social Sciences, 2019)
The learning process of productive vocational programs has a strategic role in nurturing 21